Praktik Pembuatan Modul dengan Pendekatan Deep learning dan Cinta Berbasis AI Bagi Guru PAI di KKG PAI SD Sungai Raya Kab. Kubu Raya - Syukri, M.; Alhabsyi, Zulfi Farhan; Rafida, Alifa Ihfazna; Kholik, Abdul; Faisol; Nugraha, Muhamad Tisna (Belalek, 2025)
ABSTRACT This community service activity focuses on improving the competence of Islamic Religious Education (PAI) teachers in designing teaching modules which are carried out at KKG PAI SD, Sungai Raya District, Kubu Raya Regency. The main goal is to train teachers to integrate three important concepts: deep learning approaches, love (compassion-based pedagogy), and the use of artificial intelligence (AI) technology, specifically the NotebookLM platform. This study uses a qualitative descriptive method with a participatory training approach to 12 PAI teachers at KKG PAI SD Sungai Raya, located at SDN 07 Sungai Raya. The preparation stage includes the preparation of training designs, instruments, and the preparation of source documents and the NotebookLM application. The training consisted of theoretical lectures, demonstrations of the use of AI, and direct assistance in making modules. Evaluation is carried out through pre-test, post-test, module product assessment, and activity reflection. Data collection techniques include questionnaires, observations, and documentation. Data analysis is carried out through reduction, presentation, and conclusion drawn. The validity of the data was checked by triangulation of techniques and sources, participant confirmation, and peer discussion. The report concludes that training activities can improve the competence of PAI teachers in integrating the concepts of deep learning approaches, love, and artificial intelligence (AI) technology.